2007
DOI: 10.1002/jssc.200600527
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a stereoselective HPLC method for the determination of the in vitro transport of nateglinide enantiomers in rat intestine

Abstract: A simple stereoselective high performance liquid chromatographic method was developed for the determination of the in vitro transport of the enantiomers of nateglinide (N-(trans-4-isopropylcyclohexyl-carbonyl)-phenylalanine) in the rat intestine using a Chiralcel OJ-RH column (150 x 4.0 mm, 5 microm). The effects of the mobile phase composition, pH, the flow rate, and the temperature on the chromatographic separation were investigated. The enantioseparation was achieved at 33 degrees C using a mobile phase con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Furthermore the relative bioavailability (F) of NTG-NLC was assessed by establishing the ratio between the AUC of NTG-NLC and AUC of NTG suspension. [41,42] Relative Bioavailability (F)…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Furthermore the relative bioavailability (F) of NTG-NLC was assessed by establishing the ratio between the AUC of NTG-NLC and AUC of NTG suspension. [41,42] Relative Bioavailability (F)…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Another paper showed that enantioseparation of nateglinide and its enantiomer was achieved at ambient temperature on a Chiralcel OD-R column (Qi et al, 2003). The in vitro transport of the enantiomers of nateglinide in the rat intestine was determined by chiral HPLC using a Chiracel OJ-RH column (Maddi et al, 2007). Molecularly imprinted polymers (MIP) and monolithic moleculary imprinted polymers were used as chiral stationary phase for the determination of nateglinide and its L-enantiomer (Yang et al, 2004;Yin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic separation of enantiomers can be achieved either by forming diastereoisomers by chiral derivatization agents or by using a chiral stationary phase [27]. The use of chiral derivatization agent requires a functional group in the analyte such as an amine, hydroxyl, carboxyl, carbonyl etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, cellulose, amylose ester and carbamate polymer derivatives coated onto a large pore silica backbone have proven to be most successful for chiral resolution using a range of mobile phases from polar to non-polar [28; 32-33]. Commercial columns containing these CSPs include Chiralcel OD [cellulose tri (3 [27,30].…”
Section: Introductionmentioning
confidence: 99%